Spontaneous Tumor Lysis Syndrome in an Infant: A Case Report - Shenoy, Mamatha T. (Indian J Clin Biochem, 2015)
Tumor lysis syndrome has been observed in patients with malignancies with high cellular burden and high cell turnover, tumor sensitive to therapy, especially after initiating medical treatment. It very rarely occurs spontaneously. The case described here is of 6 months male infant who presented with fever since 1 month and loose stools associated with blood since 15 days. The laboratory investigations showed lactate dehydrogenase (LDH) of 6,192 IU/L and serum uric acid 18.2 mg/dl along with pancytopenia. The infant presented with electrolyte abnormalities and renal failure.